2017
DOI: 10.1007/s13238-017-0377-7
|View full text |Cite
|
Sign up to set email alerts
|

The minor collagens in articular cartilage

Abstract: Articular cartilage is a connective tissue consisting of a specialized extracellular matrix (ECM) that dominates the bulk of its wet and dry weight. Type II collagen and aggrecan are the main ECM proteins in cartilage. However, little attention has been paid to less abundant molecular components, especially minor collagens, including type IV, VI, IX, X, XI, XII, XIII, and XIV, etc. Although accounting for only a small fraction of the mature matrix, these minor collagens not only play essential structural roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
173
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(179 citation statements)
references
References 121 publications
3
173
0
3
Order By: Relevance
“…This collagen type was detected as upregulated in human skin keloid formation . The major function of collagen VI is probably as an anchoring meshwork connecting collagen fibers to the surrounding matrix, but the precise role of collagen VI in cartilage has not been clearly defined . Veidal et al suggested that collagen VI turnover is a central player in liver fibrogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This collagen type was detected as upregulated in human skin keloid formation . The major function of collagen VI is probably as an anchoring meshwork connecting collagen fibers to the surrounding matrix, but the precise role of collagen VI in cartilage has not been clearly defined . Veidal et al suggested that collagen VI turnover is a central player in liver fibrogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…24 The major function of collagen VI is probably as an anchoring meshwork connecting collagen fibers to the surrounding matrix, but the precise role of collagen VI in cartilage has not been clearly defined. 25 Veidal et al suggested that collagen VI turnover is a central player in liver fibrogenesis. 26 Moreover, the C- terminate peptide of collagen VI chain alpha 3 (endotrophin) is known to promote phenotypic modulation and proliferation of cells.…”
Section: Collagen IIImentioning
confidence: 99%
“…Col X is highly expressed in hypertrophic chondrocytes found in OA cartilage (Luo et al 2017). Approximately 45% of collagens produced by hypertrophic chondrocytes are Col X (Shen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…From these 43 proteins, 33 were significantly increased and 10 were significantly decreased. The upregulated proteins include several typical structural proteins of the cartilage ECM, including perlecan (33), the three alpha chains of type VI collagen (34) or tenascin (35), and also many different glycolytic enzymes, such as glyceraldehyde- Supplemental Table S2). We identified 35 metabolites in OA samples that showed significant discrimination between days 2 and 14 ( Figure 3, p < 0.05).…”
Section: Differentially Expressed Proteins During the Chondrogenesis mentioning
confidence: 99%